2022
DOI: 10.3389/fimmu.2022.799454
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Overlapping Syndrome of Anti-NMDAR Encephalitis and MOG Inflammatory Demyelinating Disease in a Patient With Human Herpesviruses 7 Infection

Abstract: ObjectivesThis study reported a case of overlapping anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis and myelin oligodendrocyte glycoprotein (MOG) inflammatory demyelinating disease with human herpesviruses 7 (HHV-7) infection.MethodsThe detailed clinical characteristics, neuroimaging features, and outcomes of the patient were collected. Polymerase chain reaction (PCR), cell-based assay (CBA) and the tissue-based indirect immunofluorescence assay (TBA) were used for diagnosis.ResultsThe clinical manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The immune cells may attack the antigens of MOG and NMDAR when targeting oligodendrocytes, and subsequent generate corresponding antibodies in CSF and serum (8). Indeed, several cases have recently reported the co-occurrence of antibodies against both MOG and NMDAR (9)(10)(11). Hence, a new emerging concept referring to the coexistence of anti-MOG and anti-NMDAR antibodies is called MOGAD and anti-NMDAR encephalitis overlapping syndrome (MNOS) (11).…”
Section: Discussionmentioning
confidence: 99%
“…The immune cells may attack the antigens of MOG and NMDAR when targeting oligodendrocytes, and subsequent generate corresponding antibodies in CSF and serum (8). Indeed, several cases have recently reported the co-occurrence of antibodies against both MOG and NMDAR (9)(10)(11). Hence, a new emerging concept referring to the coexistence of anti-MOG and anti-NMDAR antibodies is called MOGAD and anti-NMDAR encephalitis overlapping syndrome (MNOS) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Patients' ages ranged from 26 to 52, with a median of 35 years and only one female. The mortality was 14.2%, and ganciclovir was given to 6 patients [4][5][6][7][8][9]. Ganciclovir and foscarnet were recommended in immunocompromised patients with HHV-6 infection [10], but the treatment of encephalitis associated with the human herpesvirus-7 infection is still limited and unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is the most common autoimmune-mediated encephalitis characterized by the manifestation of abnormal behavior, psychosis, seizures, abnormal movement, insomnia, and irritability ( 1 ). A few studies reported anti-NMDAR encephalitis overlapping with neuromyelitis optica spectrum disorders, acute demyelinating encephalomyelitis, and myelin oligodendrocyte glycoprotein (MOG) inflammatory demyelinating disease ( 2 , 3 ). Nevertheless, anti-NMDAR encephalitis associated with multiple sclerosis (MS) is rare.…”
Section: Introductionmentioning
confidence: 99%